Twenty-year follow-up of a pilot/phase II trial on the Bonn protocol for primary CNS lymphoma - Seidel, Sabine; Pels, Hendrik; Schlömer, Sabine; Kowoll, Annika; Fliessbach, Klaus; Engert, Andreas; Vogt-Schaden, Maria-Elisabeth; Egerer, Gerlinde; Reichmann, Heinz; Schackert, Gabriele; Kroschinsky, Frank; Deckert, Martina; et al. (Neurology, 2020)
Objective To determine whether a fraction of patients with primary CNS lymphoma (PCNSL) had been cured by systemic and intraventricular methotrexate- and cytarabine-based chemotherapy (Bonn protocol) after a very long-term follow-up of nearly 20 years. - Methods Sixty-five patients (median age 62 years, range 27-75; median Karnofsky performance score 70, range 20-90) had been treated with systemic and intraventricular polychemotherapy without whole brain radiotherapy from September 1995 until December 2001. All patients still alive in 2019 were contacted and interviewed on their current life situation. - Results Median follow-up for surviving patients was 19.6 years (17.5-23.3 years). Out of 65 patients, 11 (17%) were still alive. Six of those never experienced any relapse. For the whole study population, median overall survival (OS) was 4.4 years (95% confidence interval [CI] 2.9-5.9); for patients ≤60 years, 11.0 years (95% CI 4.8-17.0). The 10-year OS rate for the entire cohort was 29% and the estimated 20-year OS rate was 19%. Four late relapses were observed after 9.8, 10.3, 13.3, and 21.0 years. - Conclusion At a median follow-up of 19.6 years, 17% of patients were alive and free of tumor; however, even after response for decades, an inherent risk of relapse, either systemic or cerebral, characterizes the biology of PCNSL. - Classification of evidence This work provides Class III evidence that PCNSL treatment with methotrexate-based polychemotherapy including intraventricular therapy is associated with long-term disease control in some patients.